2022
DOI: 10.1177/11786329211066403
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Practices, and Challenges of Pharmaceuticals Inventory Control Among Pharmacy Professionals Working in Selected Public Health Facilities of West Arsi Zone, Oromia, Ethiopia

Abstract: Background: Good pharmaceutical inventory control enables health facilities (HFs) to provide complete health care by ensuring the availability of safe, effective, and affordable pharmaceuticals and related supplies of the required quality, inadequate quantity, at the required place and at all times. It boosts patients’ trust in the HFs and motivates working staff. However, it needs well-trained and skilled professionals. The aim of the current study was, therefore, assessing knowledge, practice, and challenges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…[27] This result shows no relation between the study results of Jobira, where 15% of the overall respondents are unaware of the inventory management tools. [21] Studies show that a combination of the ABC-VED or XYZ-FSN matrix often had a better impact on the management of the inventory than using a single method. [10,11] The drug procurement methods and frequency of emergency purchasing were all similar to one another.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[27] This result shows no relation between the study results of Jobira, where 15% of the overall respondents are unaware of the inventory management tools. [21] Studies show that a combination of the ABC-VED or XYZ-FSN matrix often had a better impact on the management of the inventory than using a single method. [10,11] The drug procurement methods and frequency of emergency purchasing were all similar to one another.…”
Section: Discussionmentioning
confidence: 99%
“…[30] And based on the study conducted in Ethiopia, the challenges that are quoted as a theme are taken as an important challenges for this study such as managerial role, price and budgeting, poor training and knowledge, and inadequate human resources to work. [21] It is a crucial process to plan, organize, lead, and process management-related work with fewer human resources. Studies show that 13.6 % of pharmacists spend time in managerial roles like administration, organizing, or planning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the core of the pharmaceutical supply chain is inventory control. The goals of health institutions cannot be achieved without beneficial action (Jobira et al, 2022). Moreover, Kefale and Shebo (2019) revealed that inadequate inventory management in pharmacies affects the availability of essential drugs, with an overall availability of 76.3%.…”
Section: Inventory Management and Its Importancementioning
confidence: 99%